2021
DOI: 10.3390/ijms22147605
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Type 2 Diabetes in Patients with SARS-CoV-2 Infection

Abstract: COVID-19 infection poses an important clinical therapeutic problem, especially in patients with coexistent diseases such as type 2 diabetes. Potential pathogenetic links between COVID-19 and diabetes include inflammation, effects on glucose homeostasis, haemoglobin deoxygenation, altered immune status and activation of the renin-angiotensin-aldosterone system (RAAS). Moreover, drugs often used in the clinical care of diabetes (dipeptidyl peptidase 4 inhibitors, glucagon-like peptide 1 receptor agonists, sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 133 publications
(195 reference statements)
0
20
0
Order By: Relevance
“…Additionally, TKT activity is enhanced in diabetes patients [ 19 , 20 , 21 ] and diabetes patients are at a high risk from COVID-19 [ 4 , 5 , 6 ]. Given the potential role of TKT in SARS-CoV-2 replication identified here, elevated TKT levels may be one of the factors that predispose diabetes patients to experience severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, TKT activity is enhanced in diabetes patients [ 19 , 20 , 21 ] and diabetes patients are at a high risk from COVID-19 [ 4 , 5 , 6 ]. Given the potential role of TKT in SARS-CoV-2 replication identified here, elevated TKT levels may be one of the factors that predispose diabetes patients to experience severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic disorders and diabetes are associated with an increased risk of severe COVID-19 [ 4 , 5 , 6 ]. Increased amounts of glucose in the sera of COVID-19 patients were correlated with poor prognosis in individuals both with and without pre-existing diabetes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Esam Z. et al Also showed that the use of metformin could reduce the risk of lung fibrosis associated with SARS-Cov-2 (Esam 2020 ). There are numerous other studies in this area, all of which suggest that metformin may be a useful adjunctive therapy for COVID-19 patients (Bhutta et al 2021 , Bielka et al 2021 , Ibrahim et al 2021 , Varghese, Samuel et al 2021, Zangiabadian et al 2021 ).…”
Section: Metformin and Therapeutic Goalsmentioning
confidence: 99%
“…However, T2DM therapy should be designed in accordance with local guidelines while taking personal parameters and comorbidities into account; therefore, current therapeutic regimens for the management of T2DM are not discussed here. Recent review articles about the management of COVID-19 in patients with T2DM have been published elsewhere [ 158 , 159 , 160 ].…”
Section: Prognosis Of T2dm Patients With Covid-19mentioning
confidence: 99%